Electrode reaction of Desulfovibrio desulfuricans modified with organic conductive compounds - Park, DH; Kim, BH; Moore, B; Hill, HAO; Song, MK; Rhee, HW (CHAPMAN HALL LTD, 1997)
Desuliovibrio desulfuricans M6 did not grow when polyviologen or N,N,N',N'-tetracyano-p-quinodimethane (TCNQ) was added in its growth medium. D. desulfuricans M6 with added polyviologen and TCNQ showed different cyclic voltammograms from those of TCNQ or polyviologen, whilst the intact cells were electrochemically inactive. The height of the reducing peaks in cyclic voltammogram of M6 modified with polyviologen were decreased significantly by the addition of H-2. A current was produced when the biofuel cell using polyviologen-modified M6 cells as the catalyst was gassed by H-2. These results show that the membranes of bacterium became electrically conductive by the addition of the conductive organic compounds.
Keywords: HYDROGENASE